Student interaction and the role of the teacher in a state virtual high school: what predicts online learning satisfaction?. Issue 1 (1st January 2020) - Zhang, Yining; Lin, Chin-Hsi
ABSTRACT: As online K–12 education continues to expand, concerns about its quality have taken centre stage. This study utilised online learning satisfaction as an outcome indicator for the success of online learning, and investigated student- and teacher-level factors that affected it among 226 high school students taking online world language courses from 15 teachers at a Midwestern virtual school in the US. Hierarchical linear modelling revealed that, at the student level, learner–content interaction was the only significant predictor of satisfaction; while at the teacher level, satisfaction was positively and significantly correlated with teachers' adoption of pedagogical roles, but negatively predicted by their adoption of managerial ones. The findings particularly highlight the importance of content-based teaching and learning in the context of K–12 world language learning.